Regulatory Model for the Use of Artificial Intelligence in Notarial Legal Documents in the Era of Digital Transformation - Dian Fitriana; M. Hadi Shubhan; Rosa Ristawati; Mas Rahmah (Prodi Tata Negara (Siyasah) IAIN Langsa, 2026)
The use of Artificial Intelligence (AI) in notarial services is becoming increasingly important in the era of digital transformation. However, previous studies have mainly focused on the opportunities offered by digitalization and have not sufficiently addressed the legal conflicts arising from the use of AI in Indonesian notarial practice. This study aims to analyze the legal challenges of AI implementation in notarial services and to propose a regulatory model that supports legal certainty, accountability, and personal data protection. This research uses a normative juridical approach through statutory, conceptual, and comparative analyses. The study examines the Law on Notarial Office, the Electronic Information and Transactions Law, and the Personal Data Protection Law, supported by relevant legal literature and international developments regarding AI governance. The results show that Indonesian notarial regulations have not fully adapted to technological developments. While the Electronic Information and Transactions Law recognizes electronic documents and digital signatures, the Law on Notarial Office still requires conventional notarial procedures, creating regulatory inconsistency and legal uncertainty. The study also finds that the use of AI in notarial practice raises challenges related to legal responsibility, transparency, cybersecurity, and personal data protection. This study proposes an AI-assisted notarial regulatory model based on three principles: recognition of electronic notarial services, human supervision over AI systems, and stronger personal data protection mechanisms. The study contributes to the development of cyber notary regulation in Indonesia by positioning AI as a supporting tool under the responsibility and control of the notary.